2007
DOI: 10.2105/ajph.2006.092890
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sociodemographics and Safety Belt Use in States With and Without Primary Enforcement Laws

Abstract: Primary enforcement laws are an effective population-based strategy for reducing disparities in safety belt use and may, therefore, reduce disparities in crash-related injuries and fatalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 34 publications
2
38
2
Order By: Relevance
“…CDC has shown that primary enforcement laws are associated with reduced disparities in seat belt use by gender, race, education, income, age, population density (i.e., rural vs. urban), and body mass index (Beck, Shults, Mack, & Ryan, 2007). Several studies have shown that primary laws are associated with reductions in or elimination of racial disparities in belt use (Briggs et al, 2006;Beck, Shults et al, 2007;Wells, Williams, & Farmer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…CDC has shown that primary enforcement laws are associated with reduced disparities in seat belt use by gender, race, education, income, age, population density (i.e., rural vs. urban), and body mass index (Beck, Shults, Mack, & Ryan, 2007). Several studies have shown that primary laws are associated with reductions in or elimination of racial disparities in belt use (Briggs et al, 2006;Beck, Shults et al, 2007;Wells, Williams, & Farmer, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…The estimated elasticity coefficient for auto insurance liability minimum per accident ranges from 0.096 to 0.109, implying that a ten percent increase in auto insurance minimums is associated with about one percent increase in the traffic fatality rate, on average. In other words, a $6,000 increase in per-accident liability minimum is likely to result in 11 See Viscusi (2008) for a review of life valuation methods and findings. 61 one more traffic fatality.…”
Section: Resultsmentioning
confidence: 99%
“…Our average elasticity estimate of about 0.1 implies that a $6,000 mandated on the road again: traffic fatalities and auto insurance minimums public sector economics 42 (1) 45-65 (2018) 60 increase in the auto insurance per-accident liability minimum is likely to result in one extra death from traffic collisions, on average. This mandatory increase in coverage comes at a high social cost considering that the median value of a statistical life estimated in the wage-risk studies 11 to be about $7 million. A couple of recent papers find corroborating evidence of costly moral hazard responses to changes in auto insurance coverage for drivers.…”
Section: Empirical Model and Estimatesmentioning
confidence: 99%
“…Primary seat belt use laws, where a driver can be stopped and ticketed for not using a seat belt, are highly effective with drivers of all ages (Shults, Nichols, Dinh-Zarr, Sleet, & Elder, 2004) including young drivers (Carpenter & Stehr, 2007). Secondary use laws, where ticketing for seat belt nonuse occurs only when a vehicle is stopped for other reasons, are less effective and more difficult to enforce (Beck et al, 2007;. Generally, enforcement increases use rates Solomon, Nissen, & Preusser, 1999), particularly in combination with public information campaigns (Poole, Kumpfer, & Pett, 2001;Wells, Malenfant, Williams, & Van Houten, 2000).…”
Section: Translation Issues Regarding the Promotion Of Seat Belt Use mentioning
confidence: 99%
“…In the university subsample (ages 17 through 22), two thirds of the students reported that it was necessary to use seat belts, 31% reported that they always buckled up in urban areas, and 38% reported that they used seat belts in rural areas. These rates are much lower than those reported in the United States, Canada, and Western Europe, and lower than in many other developed and developing countries (Ali Aba Hussein & El-Zobeir, 2007;Beck, Shults, Mack, & Ryan, 2007;Cunill, Gras, Planes, Oliveras, & Sullman, 2004;Derrig, Segui-Gomez, Abtahi, & Liu, 2002;Ekman, Welander, Svanstrom, & Schelp, 2001;Steptoe et al, 2002). Increasing seat belt use is one safety goal with implications for reducing motor vehicle crash injuries.…”
mentioning
confidence: 91%